Excavations on the site of the Roman town at Wroxeter, Shropshire, in 1912 - Plunkett Bushe-Fox, Joscelyn (Reports of the Research Committee of the Society of Antiquaries of London, 1913)
This is an account of the excavations on the site of the Roman Wroxeter in Shropshire, England, undertaken in 1912. Included are descriptions of artefacts such as pottery and human remains, together with an account of the methodology used to unearth these.